Investigating the contribution of foreign direct investment to coffee crop production - KANYANA, Aline (KDI School, 2023)
This paper uses a mixed methodology to investigate the contribution of FDI to coffee crop production in Burundi and what can be done to attract FDI in the coffee sector. It also examines the major causes of the decline in coffee production, its causes. Time series data analysis from 1980 to 2021 was used to track the annual production levels and exports and to determine the extent of the decline in production. From the analysis of the collected data, the study finds that 1) the main reasons for the coffee production decline were high cost of production, the aging of coffee trees, and marginal competition. 2) The benefits to Burundi in increasing coffee production included contributions to the national GDP and job creation. 3) The main contribution from FDI that can increase coffee production is strengthening cooperatives' governance and management practices, distributing improved inputs, replanting coffee trees, and increasing the number of wet mills or coffee washing stations in leading coffee-producing regions. 4) Government regulation (no investor ownership), corruption, and competition were the main barriers to FDI in Burundi, and 5) Burundi’s actions to attract FDI and improve the investment climate were good governance and a stable and reasonable exchange rate. This paper proposes strategies to adopt and upgrade the skills using TOWS frameworks, keep on training farmers, motivate youth who work in the sector, assure transparency, and ensure that all coffee companies together can achieve the expected results.
Thesis(Master) -- KDI School: Master of Public Management, 2023
Keywords: Coffee industry--Burundi; Investments, Foreign--Burundi